2016
DOI: 10.1097/spv.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Technology in Assessment of Lower Urinary Tract Symptoms: A Randomized Trial of Electronic Versus Paper Voiding Diaries

Abstract: The use of an EVD is acceptable and reliable in our population of adult female patients with lower urinary tract symptom. Electronic voiding diary and PVD have good test-retest reliability, although the number of voids and leaks entered is slightly lower for the EVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Consequently, they found that eDM3d was a useful tool easily filled in by patients with a high satisfaction rate. Sussman et al [ 14 ] conducted a randomized trial comparing a web app (BladderTrakHer) developed by the American Urogynecologic Society to the conventional paper-based VD for reliability and satisfaction. They found that BladderTrakHer and the paper-based VD had good test-retest reliability, although the number of voids and leaks entered was slightly lower for the electronic VD (28.0 vs. 25.5 [ p = 0.03] and 4.5 vs. 2.8 [ p = 0.02], respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they found that eDM3d was a useful tool easily filled in by patients with a high satisfaction rate. Sussman et al [ 14 ] conducted a randomized trial comparing a web app (BladderTrakHer) developed by the American Urogynecologic Society to the conventional paper-based VD for reliability and satisfaction. They found that BladderTrakHer and the paper-based VD had good test-retest reliability, although the number of voids and leaks entered was slightly lower for the electronic VD (28.0 vs. 25.5 [ p = 0.03] and 4.5 vs. 2.8 [ p = 0.02], respectively).…”
Section: Discussionmentioning
confidence: 99%
“…They found that BladderTrakHer and the paper-based VD had good test-retest reliability, although the number of voids and leaks entered was slightly lower for the electronic VD (28.0 vs. 25.5 [ p = 0.03] and 4.5 vs. 2.8 [ p = 0.02], respectively). However, in these previous studies, apps were used only to facilitate patient fulfillment or improve compliance [ 11 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This potential diagnostic alternative is particularly noteworthy in view of growing investigative interest in adjunctive strategies to voiding diary analysis in order to facilitate a more patient-centered approach to nocturia evaluation and management. 146151…”
Section: Emerging Technologies: Individualizing Nocturnal Polyuria Di...mentioning
confidence: 99%
“…This potential diagnostic alternative is particularly noteworthy in view of growing investigative interest in adjunctive strategies to voiding diary analysis in order to facilitate a more patient-centered approach to nocturia evaluation and management. [146][147][148][149][150][151] Even among patients who share a common diagnosis nocturnal polyuria, the composition of their nocturnal urine is highly variable, 117,152,153 such that most nocturnal polyuria patients can be further phenotyped as having (a) excess free water diuresis, (b) excess solute diuresis, or (c) mixed water/solute diuresis 74,154 (Figure 1). Phenotyping patients by the composition of their excess urine volume -the relevant substrate for pharmacologic interventions directed at nocturnal polyuria -carries the potential to directly facilitate individualized treatment.…”
Section: Emerging Technologies: Individualizing Nocturnal Polyuria Di...mentioning
confidence: 99%
“…As new therapeutics are tested, the Guidelines of the International Headache Society for controlled trials of preventive treatment of migraine in adults and children recommend prospective collection of a headache diary that captures migraine symptoms (5,6). Historically, headache diaries have been done on paper, but studies in other patient populations have described equivalent to increased diary completion rate and participant retention with electronic diaries (7)(8)(9). One review of adherence between headache diary modalities suggested increased adherence to electronic diaries, though technical problems were a clear barrier (10).…”
Section: Introductionmentioning
confidence: 99%